2010
DOI: 10.1007/s11274-010-0425-4
|View full text |Cite
|
Sign up to set email alerts
|

A quick screening method to identify β-glucosidase activity in native wine yeast strains: application of Esculin Glycerol Agar (EGA) medium

Abstract: One hundred and fifty-four yeast strains were isolated from grapes and musts of Uruguayan vineyards and wineries. Only thirty strains showed b-glucosidase activity in Esculin Glycerol Agar (EGA) solid medium. Twenty-one were non-Saccharomyces and nine were Saccharomyces cerevisiae strains. The objective of this study was to evaluate the suitability of Esculin Glycerol Agar (EGA) solid medium for screening b-glucosidase activity in native yeasts strains. Halo sizes measured in the EGA solid medium were correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 43 publications
0
36
0
4
Order By: Relevance
“…Although arbutin and esculin derivatives were the most reliable β-glucosidic grape analogues, no studies have correlated these assays with the natural grape glucosides hydrolysis capability by wine-related yeasts (Pérez et al, 2011), as the piceid substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although arbutin and esculin derivatives were the most reliable β-glucosidic grape analogues, no studies have correlated these assays with the natural grape glucosides hydrolysis capability by wine-related yeasts (Pérez et al, 2011), as the piceid substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Pérez et al (2011) showed that it is important to create collections of native wine yeasts, since very few strains with β-glucosidase activity have been identified. In fact, the above restricts knowledge of their winemaking potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following enzymatic activities were assessed: P-D-glucosidase (16,19,25,35), pectolytic and xylanolytic activities (7), protease (44), ester hydrolase and glycosidase (16), and (3-D-xylosidase (25). (3-D-Glucosidase, pecto lytic, and xylanolytic activities were also studied at wine pH and wine ethanol concentration.…”
Section: Methodsmentioning
confidence: 99%
“…b-glucosidase activity of some S. cerevisiae strains has been detected during winemaking indicating the potential of the starter culture to improve the sensorial profile of wine (Hernàndez et al 2003;Tosi et al 2009). The great diversity of S. cerevisiae strains in grapes and wines is well documented and some screening methods for glucosidase activity able to correlate with real wine conditions were recently proposed (Perez et al 2010).…”
Section: Introductionmentioning
confidence: 99%